Motivasi Lingkungan Keluarga Mempengaruhi Karakter dan Hasil Belajar Siswa Tingkat Sekolah Dasar - Yati, Yuni; Wulandari, Murfiah Dewi; Darsinah, Darsinah (Lembaga Yasin AlSys, 2022)
The purpose of this study was to discuss the motivation of the family environment affecting the character and learning outcomes of elementary school students. Basically, the environment is very influential in shaping a person's attitude and personality, and because each child is a unique person, the family environment and its motivations also affect children's learning behavior. If the child is in a good environment, it will have a positive impact on personality development, learning behavior and education. The purpose of this study is to clarify how much parental motivation can affect the character and learning outcomes of elementary school students. This research was conducted through a literature study, taking into account the results of related journals available in electronic media. The conclusions of this article are as follows: Motivation The family environment plays an important role in shaping the character of basic education students, a harmonious home environment fully supports the process of developing the personality character and learning behavior of children, thus enabling optimal learning outcomes.